DISCURSIVE CO-OPTATION AND STRUCTURAL DOMINATION IN THE RECONSOLIDATION OF AUTHORITARIANISM IN EGYPT AFTER THE ARAB SPRING - Sangidu Sangidu; Imam Wicaksono; Sherif Sa'ad Al-Gayyar (Arabic Literature Department, 2025)
This study aims to analyze the failure of Egypt’s democratic transition after the fall of Hosni Mubarak, emphasizing the dynamics of authoritarian resilience and discursive co-optation in shaping the pseudo-legitimacy of the post-revolution regime. Integrating Gramsci’s theory of political hegemony with the Egyptian context as the novelty of this research, it also addresses how democratic symbols were reappropriated to sustain authoritarian control an issue significant for understanding democratic backsliding in the Global South. Employing a qualitative, historical-critical case study, this library-based research systematically reviews academic literature, media archives, and international reports. Data were analyzed through Gramscian-themed coding and critical discourse analysis to uncover mechanisms of dominance and ideological manipulation. The findings reveal that although the revolution succeeded in overthrowing Mubarak’s regime, the entrenched structures managed to reclaim control through structural repression and the co-optation of discourse. The implications highlight the importance of interpreting democratic backsliding as a multidimensional process that combines material control with symbolic domestication.